Perbedaan Nilai Kapasitas Vital (Kv) Paru Pada Laki-Laki Antara Pekerja Pabrik Kayu Dan Pekerja Kantoran Di Sukoharjo - Aulia, Hasna Habiba; , Dr. Sri Wahyu Basuki., M. Kes (2017)
Introduction : Dust pollution at workplace had an impacted to the occurrence of lung disesases related work. The impacted of exposure dust at the factory work could decrease lung function. One of the indicators value of Vital Capacity (VC) lungs were examined by spirometry. CV value reflects the changes of maximum volume that can occured in the lungs. CV value on dust-exposed factory workers decreased due to the mechanism of irritation and inflammation in the respiratory tract caused by dust. Purpose : To determined the differences in Vital Capacity (CV) between wood factory male workers and officeman workers. Methods : The study design was observational analytic methode with cross sectional approachment, the sampling method was purposive sampling technique. The size of sampel was 30 per group. The total sample was 60 manworkers who qualified the restriction criteria. The measuring instrument we used were spirometry 'Bionet'. The data analyzed use hypothesis testing which was the t test two unpaired and Mann-Whitney with SPSS 20.0 program for windows. Research results : Based on data analysis could be seen that there was a significant difference between the value of lung vital capacity (CV) between the wood factory male workers and officeman workers with a p-value is 0.002. Conclusion : This study concluded that there were significant differences of lung Vital Capacity (CV) values between the wood factory male workers and officeman worker.